Prediction nomogram for evaluating the probability of postoperative fever in children with acute appendicitis - Chen, Yang; Ren, Feng; Xiao, Dong; Guan, Ai-hui; Zhu, Le-dao; Ma, Xiao-peng; Wang, Zhi-yong (Frontiers in Pediatrics, 2022)
Objective The purpose of this study was to establish a predictive model of postoperative fever in children with acute appendicitis through retrospective analysis, and the prediction ability of the model is demonstrated by model evaluation and external validation. Methods Medical records information on children undergoing surgery for acute appendicitis within 2 years were retrospectively collected, prospective collection was performed for external validation in the next 3 months. The patients were divided into two groups according to whether the postoperative body temperature exceeded 38.5℃. Multivariate logistic regression analysis was used to determine independent risk factors and develop regression equations and nomogram. ROC curve, calibration curve and decision curve were made for model evaluation. Finally, the clinical implication of the prediction model was clarified by associating postoperative fever with prognosis. Results High risk factors of postoperative fever included in the prediction model were onset time(X1), preoperative temperature(X2), leukocyte count(X3), C-reactive protein(X4) and operation time(X5). The regression equation is logit(P) =0.005X1 + 0.166X2 + 0.056X3 + 0.004X4+ 0.005X5-9.042. ROC curve showed that the area under the curve (AUC) of the training set was 0.660(0.621,0.699), and the AUC of the verification set was 0.712 (0.639,0.784). The calibration curve suggested that the prediction probability was close to the actual probability. Decision curve analysis (DCA) showed that patients could benefit from clinician's judgment. Furthermore, prognostic analysis showed children presenting with postoperative fever had the more duration of postoperative fever, hospitalization stays and cost, except for rehospitalization. Conclusion All the results revealed that the model had good predictive ability. Pediatricians can calculate the probability of postoperative fever and make timely interventions to reduce pain for children and parents.